Komposisi mineral mikro dan logam berat pada ikan bandeng dari tambak Tanjung Pasir Kabupaten Tangerang - Tati Nurhayati; Nurjanah .; Alfi Hamdan Zamzami (Depik, 2014)
The purpose of this study is to determine the micro minerals composition i.e. iron, zinc, copper, and iodine) and heavy metals i.e. lead, cadmium, and mercury) on three groups of weight of milkfish (Chanos chanos). Micro minerals and heavy metals were analyzed using atomic absorption spectrofotometric (AAS). The results showed that the highest levels of micro minerals were found at weight ±150 g (6.95±0.16 mg of zinc/kg of dry basis, copper 0.55±0.01 mg/kg of dry basis , and iron 12.14±0.06 mg/kg of dry basis. The highest iodine content contain was found at weight 102 g ± is 76.33±0.01 mg/100g of dry basis. The concentrations obtained in lead was 0.143±0.0057 mg/kg, cadmium was 0.0433±0.011 mg/kg, and mercury was 0.143±0.0057 mg/kg of dry basis,. The heavy metals level from Tanjung Pasir Tangerang District are safe to be comsumed since it is still below the limit for food savety.